Developing context-aware mobile applications using composition process based-on heterogeneous software entities - Djeddar, Afrah; Bendjenna, Hakim; Amirat, Abdelkrim; Alwan Aljuboori, Ali Amer (Design for Scientific Renaissance, 2015)
Despite the tremendous number of mobile applications (apps) that developed using various implementation forms such as component, service, or app, user’s needs are unlike each other. Besides, mobile devices are characterized by heterogeneous software and hardware configurations. Developing customized mobile applications needs to explore and incorporate new entities in the surrounding user context. Besides, involving the existing heterogeneous entities might benefit in developing context-aware mobile apps. Thus, a significant challenge in the development process of mobile apps is the deployment of these applications in the heterogeneous devices available on the market. To tackle these challenges, there is a need for a composition process to reuse and utilize the existing heterogeneous entities to develop mobile apps according to user’s requirements. Hence, the behavior of the desired apps can be customized according to the user context information. This paper addresses the issue of discovering, integrating and reusing the existing heterogeneous software entities in developing a customized mobile application. In this paper we propose framework for context-aware mobile apps composition process based-on existing heterogeneous software entities.